Conditioned pain modulation affects the N2/P2 complex but not the N1 wave: A pilot study with laser‐evoked potentials. (28th November 2020) - Squintani, Giovanna; Rasera, Andrea; Segatti, Alessia; Concon, Elisa; Bonetti, Bruno; Valeriani, Massimiliano; Tinazzi, Michele
Abstract: Background: The 'pain‐inhibits‐pain' effect stems from neurophysiological mechanisms involving endogenous modulatory systems termed diffuse noxious inhibitory controls (DNIC) or conditioned pain modulation (CPM). Laser‐evoked potentials (LEPs) components, the N2/P2 complex, and the N1 wave, reflect the medial and lateral pain pathway, respectively: anatomically, the lateral thalamic nuclei (LT) project mainly to the somatosensory cortex (N1 generator), while the medial thalamic nuclei (MT) are bound to the limbic cortices (N2/P2 generators). Methods: We applied a CPM protocol in which the test stimulus was laser stimulation and the conditioning stimulus was a cold pressor test. LEPs recordings were obtained from 15 healthy subjects in three different conditions: baseline, during heterotopic noxious conditioning stimulation (HNCS) and post‐HNCS. Results: We observed a significant reduction in N2/P2 amplitude during HNCS and a return to pre‐test amplitude post‐HNCS, whereas the N1 wave remained unchanged during and post‐HNCS. Conclusions: Our results indicate that CPM affects only the medial pain system. The spinothalamic tract (STT) transmits to both the LT and the MT, while the spinoreticulothalamic (SRT) projects only to the MT. The reduction in the amplitude of the N2/P2 complex and the absence of change in the N1 wave suggest that DNIC inhibition on the dorsal horn neurons affects only pain transmission via the SRT, while the neurons that give rise to the STT are not involved. The N1 wave can be a reliable neurophysiological parameter for assessment of STT function in clinical practice, as it does not seem to be influenced by CPM. Significance: No reports have described the effect of DNIC on lateral and medial pain pathways. We studied the N1 wave and the N2/P2 complex to detect changes during a CPM protocol. We found a reduction in the amplitude of the N2/P2 complex and no change in the N1 wave. This suggests that the DNIC inhibitory effect on dorsal horns neurons affects only pain transmission via the SRT, whereas the neurons that give rise to the STT are not involved.